Perceptions of the Importance of Advance Care Planning During the COVID-19 Pandemic Among Older Adults Living With HIV - Nguyen, Annie L.; Davtyan, Mariam; Taylor, Jeff; Christensen, Christopher; Brown, Brandon (Frontiers in Public Health, 2021)
Background: The importance of advance care planning (ACP) discussions have been heightened during the COVID-19 pandemic. We assessed advance directive completion, healthcare proxy (HCP), and attitudes toward ACP among older adults ages 50+ living with HIV during the COVID-19 pandemic. Methods: Internet-based surveys were administered to 100 participants residing in the Coachella Valley, California from April to June 2020. We examined self-reported completion of an advance directive, HCP, and attitudes toward ACP before and after COVID-19. Adjusted regressions were performed on attitudes toward ACP. Results: Participants' mean age was 64.2 years, most were non-Hispanic white (88.0%), men (96.0%), and identified as sexual minorities (96.0%). Many reported having an advance directive (59.6%) or HCP (67.3%). Most (57.6%) believed ACP to be more important now compared to the pre-pandemic era. Having an advance directive was associated with increase in age, higher education, living with other people, never having an AIDS diagnosis, and current undetectable viral load (p < 0.05). Having a HCP was associated with higher education, being married/partnered, and living with other people (p < 0.05). In a logistic regression model adjusted for education and living situation, the belief that ACP was more important during COVID was associated with not having an advance directive (OR: 5.07, 95% CI: 1.78–14.40) and fear of COVID-19 infection (OR: 4.17, 95% CI: 1.61–10.76.) Conclusions: The COVID-19 pandemic presents a window of opportunity to engage people aging with HIV in ACP discussions, particularly those who do not already have an advance directive.